Cellular ceramics by slip casting of emulsified suspensions. Issue 15 (December 2020) - Cesconeto, F.R.; Frade, J.R.
Graphical abstract: Highlights: Ceramics with designed cellular microstructures by emulsification of suspensions with edible oil. Versatile shaping by slip casting. Ability to minimize undue loss of porosity. Abstract: Cellular ceramics were processed by slip casting of alumina suspensions emulsified with sunflower oil. A model behavior was derived on assuming that the templating dispersed phase and its droplet size distribution are retained as porosity in the resulting cellular ceramics, whereas the continuous ceramic suspension evolves to dense struts and thin inter-pore walls. Representative values of solid load and oil to suspension ratio were selected to seek close packed spatial distribution of nearly spherical. Stirring rate and additions of surfactant were also varied for greater flexibility in adjusting droplet size and rheology of the corresponding emulsified suspensions; this also contributes to minimize undue losses of porosity, relative to the model behavior, and determines microstructural features such as size distributions and average cell size.